Current and Emerging MR Methods and Outcome in Rodent Models of Parkinson’s Disease: A Review - Petiet, Alexandra (Frontiers in Neuroscience, 2021)
Parkinson’s disease (PD) is a major neurodegenerative disease characterized by massive degeneration of the dopaminergic neurons in the substantia nigra pars compacta, α-synuclein-containing Lewy bodies and neuroinflammation. Magnetic Resonance (MR) biomarkers play a crucial role in the diagnosis and monitoring of disease progression and treatment. A variety of MR methods are available to characterize neurodegeneration and other disease features such as iron accumulation and metabolic changes in animal models of PD. This review aims at giving an overview of how those physiopahological features of PD have been investigated using various MR biomarkers in rodent models. Toxin-based and genetic-based models of PD are first described. Biomarkers of neurodegeneration, iron load and metabolism alterations are then detailed in those models. Ultimately, this review presents emerging methods of inflammation markers based on diffusion-weighted spectroscopy and of neuromelanin imaging, and future directions are suggested.